2006
DOI: 10.1002/elps.200500622
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic silica capillary column with coated cellulose tris(3,5‐dimethylphenylcarbamate) for capillary electrochromatographic separation of enantiomers

Abstract: Monolithic silica capillary columns were prepared by a sol-gel process in fused-silica capillaries with an inner diameter of 50 microm and were modified by coating of cellulose tris(3,5-dimethylphenylcarbamate). Influences of the factors in the modification process on enantiomer separations were investigated. The prepared columns were used to perform enantiomer separations by CEC. Fifteen and two pairs of enantiomers were separated under aqueous and nonaqueous mobile phases, respectively, and most of them were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…The result of baseline separation of benzoin demonstrated that the chiral selector of CDMPC was well coated onto the hybrid monolith matrices. Compared to the reported data on the CDMPC coated onto pure silica monolith [25] or organic monolith [30], the resolution and efficiency on this hybrid monolith was remarkably lower. The same result was also observed for enantioseparation of benzoin with CLC, as shown in Fig.…”
Section: Effects Of Coating Conditions On Enantioseparationmentioning
confidence: 61%
See 2 more Smart Citations
“…The result of baseline separation of benzoin demonstrated that the chiral selector of CDMPC was well coated onto the hybrid monolith matrices. Compared to the reported data on the CDMPC coated onto pure silica monolith [25] or organic monolith [30], the resolution and efficiency on this hybrid monolith was remarkably lower. The same result was also observed for enantioseparation of benzoin with CLC, as shown in Fig.…”
Section: Effects Of Coating Conditions On Enantioseparationmentioning
confidence: 61%
“…The CDMPC has been successfully coated on either native silica monolith [25] or hybrid monolith synthesized with MTMS/TMOS [37] for chiral separation. Herein, CP-silica monolith would be similarly coated with chiral selectors after straightforward modification with nucleophiles such as ethylene diamine or DETA to form NH 2 functionalities via the nucleophilic substitution reaction, which generates the stronger EOF for CEC.…”
Section: Preparation and Characterization Of Hybrid Monolithic Columnmentioning
confidence: 99%
See 1 more Smart Citation
“…86 Baseline separation of a pair of enantiomers was achieved in 90 s with high column efficiency by short-end separation under high voltage.…”
Section: ·2 Capillary Electrophoresis and Capillary Electro-mentioning
confidence: 99%
“…Very recently, the group of Zou adapted a procedure earlier proposed by Chankvetadze and co-workers for the preparation of silica monolith-based capillary columns that were modified with cellulose tris(3,5-dimethylphenylcarbamate) (CDMPC) as SO for electrochromatographic enantiomer separations of 15 neutral and basic compounds [88]. Thus, first the sol-gel-derived silica monolith was flushed with an acidic solution which should assure rehydroxylation of the silica and ascertain a reasonable silanol density because of its importance as EOF source.…”
Section: Inorganic Silica-based Monolithsmentioning
confidence: 99%